2022
DOI: 10.1002/adhm.202200340
|View full text |Cite
|
Sign up to set email alerts
|

Mucosomes: Intrinsically Mucoadhesive Glycosylated Mucin Nanoparticles as Multi‐Drug Delivery Platform

Abstract: Mucus is a complex barrier for pharmacological treatments and overcoming it is one of the major challenges faced during transmucosal drug delivery. To tackle this issue, a novel class of glycosylated nanoparticles, named "mucosomes," which are based on the most important protein constituting mucus, the mucin, is introduced. Mucosomes are designed to improve drug absorption and residence time on the mucosal tissues. Mucosomes are produced (150-300 nm), functionalized with glycans, and loaded with the desired dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Additional FA quantities can be released in large bowel as a function of the actual transit time. In addition, after FA loading, the APTES functionalized MCM-41 or MCM-48 particles can be embedded in a mucoadhesive system [ 64 , 65 ], that will allow modulation of residence time and FA recovery [ 66 ]. Furthemore, by comparing with antimicrobial drugs, such as antibiotics, the negative environmental impact is low as these systems don’t lead to antimicrobial resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Additional FA quantities can be released in large bowel as a function of the actual transit time. In addition, after FA loading, the APTES functionalized MCM-41 or MCM-48 particles can be embedded in a mucoadhesive system [ 64 , 65 ], that will allow modulation of residence time and FA recovery [ 66 ]. Furthemore, by comparing with antimicrobial drugs, such as antibiotics, the negative environmental impact is low as these systems don’t lead to antimicrobial resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Mucus is a water, protein, and lipid enriched with a viscoelastic hydrogel-like structure, and it also possesses hydrophilic and hydrophobic domains as well as the negative charge, which gives the mucus the ability to adsorb and entrap a variety of particles and molecules, including drugs and their carriers. , It was reported that the two main reasons that the mucosa BB layer affects drug absorption were an encumbering of the movement of drugs via its viscosity and mesh-like physical particle filtering barrier, and that its interaction with drugs is influenced by its complex physicochemical properties (pH, negative charge, chemical substance interactions with hydrophobic domains, etc. ). , The favorable physiochemical characteristics of nano drug delivery systems (NDDS) have achieved good experimental and clinical results in overcoming problems relating to mucus interfacing and penetration, and have mainly been explored through exploiting three strategies (mucoadhesion, mucopenetration, and mucolytics). For example, Shen et al constructed mucus-penetrating and villi-binding micelles, in which the polyzwitterion (poly­[2-(N-oxide-N,N-diethylamino)­ethyl methacrylate]; OPDEA) modification endowed the micelles with the capability to permeate through the viscous mucus to rapidly and tightly bind cells for transport. A major advantage of these micelles was that they were highly nonfouling to proteins while exhibiting weak binding to phospholipids and thereby could deliver paclitaxel efficiently for tumor treatment via oral administration .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Butnarasu et al 33 reported mucosomes (a novel class of glycosylated nanoparticles based on mucin) as a multi-drug delivery platform for pharmacological treatments. The mucosomes appeared to be resistant to proteolytic activity of intestinal proteases delaying release of encapsulated ingredient for 2 hours, which is typical duration of the intestinal digestion phase.…”
Section: Introductionmentioning
confidence: 99%